The Use of "Seven" as an English Learning Medium for 7th Grade Junior High School Students - Sulistiono, Eko; Fitriani, Enis; Pusparini, Indrawati; Mustofa, Mutmainah (BRILIANT: Jurnal Riset dan Konseptual, 2024)
This article focuses on the development of mobile learning media using Android-based applications to enhance the teaching and learning process, specifically for English language education in seventh-grade classrooms. The study follows the research and development (R&D) model proposed by Lee and Owens (2004) and was conducted in two private schools in the Malang district. The development process consists of five phases: assessment/analysis, design, development, implementation, and evaluation. The "Seven" application, developed using the Andromo platform, aims to improve the four basic skills of English language learning: reading, speaking, writing, and listening. The effectiveness of the application was evaluated through material verification and media verification, using qualitative and quantitative data analysis methods. The findings indicate that the "Seven" application was well-received by students, with positive feedback regarding its user-friendly interface and the engaging learning experience it provided. The study demonstrates the potential of Android-based mobile learning as an effective and practical tool for enhancing English language education in seventh-grade classrooms.